Elucidating the structure of melanoidins derived from biscuits: A preliminary study - Patrignani, Mariela (2023)
Melanoidins present important physiological activities, but their structure is largely unknown. The objective of the present work was to reveal the physicochemical characteristics of biscuit melanoidins(BM) prepared under high temperature(HT) and low temperature(LT) conditions (150 °C/25 min-100 °C/80 min respectively). BM were characterised and analysed by differential scanning calorimetry, X-ray and FT-IR. Moreover, the antioxidant capacity and the zeta potential were determined. The phenolic content of HT-BM was higher than that of LT-BM (19.5 ± 2.6% vs 7.8 ± 0.3% respectively, p ≤ 0.05) and the antioxidant capacity determined by ABTS/DPPH/FRAP (p ≤ 0.05) was greater. Also, HT-BM presented a 30% increase in crystal structure compared to LT-BM according to X-ray analysis. The magnitude of the negative net charge was significantly higher in HT-BM (−36.8 ± 0.6) than in LT-BM (−16.8 ± 0.1)(p ≤ 0.05). FT-IR analysis confirmed the presence of phenolic and intermediate Maillard reaction compounds bound to the HT-BM structure. In conclusion, the different heating treatments applied to biscuits led to differences in the melanoidin structure.